Primary breast diffuse large B-cell lymphoma (germinal center B-cell-like subtype): a case report and literature review - Xing, Xiaoxiao; Liao, Daixiang; Zhang, Shiyun; Li, Jun; Li, Junyi; Zhang, Ling; Wang, Yun; Zhang, Dongpo; Wang, Yue; Li, Yufei (Frontiers in Oncology, 2025)
BackgroundPrimary breast lymphoma (PBL) is a rare type of extranodal lymphoma, of which diffuse large B-cell lymphoma (DLBCL) is the most common histological subtype. Due to its nonspecific clinical and imaging features, PBL is frequently misdiagnosed as breast carcinoma or mastitis, leading to delays in treatment.Case PresentationWe report the case of a postmenopausal female who presented with a rapidly enlarging mass in the left breast and was initially misdiagnosed as non-lactational mastitis. Core needle biopsy and immunohistochemistry revealed features consistent with DLBCL of the germinal center B-cell-like (GCB) subtype. Notably, the tumor cells co-expressed Bcl-2 (95%) and c-Myc (70%), meeting the criteria for double expressor lymphoma (DEL), suggesting aggressive biological behavior. Serum lactate dehydrogenase (LDH) was markedly elevated (3902 U/L), indicating high tumor burden. Despite palliative surgery, the patient’s condition rapidly deteriorated.DiscussionGCB-type DLBCL generally carries a better prognosis than the activated B-cell-like (ABC) subtype; however, significant heterogeneity exists within the GCB subtype. DEL is recognized as a high-risk variant associated with poor outcomes, regardless of cell of origin. This case emphasizes the diagnostic challenges of PBL and highlights the need for precise immunophenotyping and individualized therapy. LDH elevation may reflect hypoxia-induced metabolic reprogramming and potential treatment resistance via the HIF-1α pathway.ConclusionAccurate diagnosis of primary breast DLBCL requires careful differential evaluation. Immunohistochemical profiling and LDH monitoring are crucial for prognostic assessment and treatment planning. More clinical data are needed to optimize management strategies for this rare entity.